Experience with NovoSorb® Biodegradable Temporising Matrix in reconstruction of complex wounds. Issue 9 (3rd June 2021) - Li, Henry; Lim, Pelicia; Stanley, Edward; Lee, Geoffrey; Lin, Sandra; Neoh, Derek; Liew, Julian; Ng, Sally Kiu‐Huen
Abstract : The NovoSorb® Biodegradable Temporising Matrix (BTM) is a synthetic polyurethane dermal matrix used to reconstruct complex wounds. In this study, we explore a case series of 35 wounds of varying indications and report on outcomes and complications. We found that BTM offers a safe and reliable reconstructive option in challenging wounds that would otherwise require more complex operations. Abstract: Background: The NovoSorb® Biodegradable Temporising Matrix (BTM) is a synthetic polyurethane dermal matrix used to reconstruct complex wounds including deep dermal and full‐thickness burns, necrotising fasciitis and free flap donor site. We hope to further explore its potential applications in this series. Methods: Patients who received BTM application across four centres over an 18‐month period were included. Patients were followed up to assess BTM and graft take, the aesthetic, the return of sensation and complications. Results: A total of 27 patients with 35 wounds were identified with a range of aetiologies. Thirty‐three wounds had 100% integration of BTM at the time of sealing membrane removal. Seven wounds had partial graft loss that later healed by secondary intention. In two cases, re‐epithelialisation occurred with BTM alone without split‐skin graft. Conclusion: BTM offers a safe and reliable reconstructive option in challenging wounds that would otherwise require more complex operations.